Studi Pemberian Diuretik Pada Pasien Sirosis Hepatik Dengan Komplikasi Asites di RSUD dr. Iskak Tulungagung. - Agies Annastasya P.D.; Alvina Arum Puspitasari; Didik Hasmono; Binti Muzayyanah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
According to the World Health Organization (WHO), cirrhosis is a structural change of the liver from normal to abnormal, characterized by fibrosis. Ascites is the most common complication in liver cirrhosis patients with the primary trigger (75%) is portal hypertension. The treatment focuses on removing the fluid from the peritoneal cavity. This study aim to understanding the pattern of diuretic use as ascites therapy in patients with cirrhosis hepatic. An observational study with a retrospective and descriptive approach using total sampling method in patients diagnosed with cirrhosis and ascites who received diuretics at Dr Iskak Tulungagung general hospital during January-December 2022 were conducted. The tools used in this study include medical records, data collection sheets, clinical data sheets, and laboratory data. Among 62 patients, 16 (26%) received spironolactone monotherapy, 9 (14%) furosemide monotherapy, 21 (34%) combination therapy, and 16 (26%) underwent switching between regimens. Spironolactone, particularly at 100 mg orally once daily, either alone or in combination with furosemide (40 mg intravenously once daily), was the most frequently prescribed diuretic regimen. These findings indicate that the therapeutic approach applied in clinical practice has generally followed the AASLD guideline recommendations.